PENGEMBANGAN BISNIS PEDAGANG SAYUR MELALUI MEDIA SOSIAL PERSPEKTIF HUKUM BISNIS ISLAM - Moch. Uzeir Mustaqfirin; Muhamad Ali Tamrin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
The background to this research is that currently technology has developed rapidly, all human activities have evenly utilized technology. Like the business activities carried out by vegetable traders in Canggu Village. They use technology to develop their business, so that people don't have to travel far to traditional markets and to take advantage of technology that is currently developing, because many people in the surrounding area still choose to shop at traditional markets. The researcher chose the object of vegetable traders because vegetables have high consequences, namely they wilt easily and rot quickly, so vegetable traders need a large marketing area in addition to offline marketing, so that the vegetables they sell run out quickly, get bigger profits and minimize losses. The aim of this research is to find out the business practices carried out by vegetable traders in Canggu Village, the influence of the use of social media on the business they run and to know the business development carried out by vegetable traders when viewed from Law Business Islamic. This type of research is field research using a qualitative descriptive approach, to collect data through observation, interviews and documentation. The results of this research are (1) that the practices carried out by vegetable traders in marketing their products are offline and online using the social media Whatsaap and Facebook (2) these media can have an influence on the business they run, one of which is that it can increase sales and income (3) in developing the vegetable trader's business are in accordance with Islamic Business Law.